Hadlanah in Limitations: exploring the fulfillment of the Rights of Scavenger Children through the Lens of Maqashid al-Shariah and Weberian Social Action - Nurulita, Fitri (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study deeply examines the practice of fulfilling children’s rights within scavenger families in Gang Rukun, Wonocatur, through the lens of Maqashid al Shariah, Max Weber’s social action theory, and international children’s rights conventions (CRC). Using a qualitative case study approach, researchers conducted in depth interviews, participant observation, and administrative document reviewing to explore family responses to economic and social pressures in fulfilling children’s basic rights: education, health, legal protection, and identity status. Findings indicate that, despite extremely limited living conditions, parents consistently strive to uphold religious elements, physical and mental safety, legitimate lineage, intelligence, and economic stability which are the main dimensions of Maqashid through meaningful actions such as value rational, instrumental rational, traditional, and affectual actions. However, the fulfillment of rights in predominantly focused on the ?ar?riyy? (primary needs) aspect, while secondary ??jiyy?t and complementary ta?s?n?yy? rights remain inadequately addressed. This research enriches the transnational discourse in Islamic law by weaving together the framework of Maqashid and universal children’s rights, and offers substantive insights for policy formulations based on social justice child protection in marginalized communities. The findings also highlight the importance of cross sectoral interventions, such as access to education, health services, and legal identity protection in supporting the synergy between Islamic norms and international conventions on children’s rights. [Penelitian ini mengkaji secara mendalam praktek pemenuhan hak anak dalam keluarga pemulung di Gang Rukun, Wonocatur, Yogyakarta, melalui lensa Maqashid al syariah, teori tindakan sosial Max Weber, dan konvensi hak anak internasional (CRC). Dengan menggunakan pendekatan kualitatif berbasis studi kasus, peneliti melakukan wawancara mendalam, observasi partisipatif, dan telaah dokumen administratif untuk menggali respons keluarga terhadap tekanan ekonomi dan sosial dalam memenuhi hak-hak dasar anak: pendidikan, kesehatan, perlindungan hukum, serta status identitas. temuan menunjukan bahwa, meskipun kondisi hidup sangat terbatas, orang tua secara konsisten berupaya menggalang elemen religius, keselamatan fisik dan mental, keturunan yang sah, kecerdasan, serta stabilitas ekonomi yang merupakan dimensi utama Maqashid, melalui tindakan bermakna seperti Value Rational, instrumental, traditional, dan affectual actions. namun, pemenuhan hak lebih banyak difokuskan pada aspek ?ar?riyy?t (kebutuhan primer), sementara hak sekunder ??jiyy?t dan pelengkap ta?s?n?yy?t tetap belum mendapatkan perhatian memadai. penelitian ini memperkaya wacana transnasional dalam hukum Islam dengan merajut kerangka Maqashid dan hak anak universal, serta menawarkan wawasan substantif untuk formulasi kebijakan berbasis keadilan sosial dan perlindungan anak di komunitas marginal. temuan ini juga menyoroti pentingnya intervensi lintas sektoral seperti akses pendidikan, layanan kesehatan, dan perlindungan hukum identitas, dalam mendukung sinergi antara norma Islam dan konvensi Internasional mengenai hak anak.]